Brain neuropeptides in central ventilatory and cardiovascular regulation in trout - Le Mével, Jean-Claude; Lancien, Frederic; Mimassi, Nagi; Conlon, John Michael (Frontiers in Endocrinology, 2012)
Many neuropeptides and their G-protein coupled receptors (GPCRs) are present within the brain area involved in ventilatory and cardiovascular regulation but only a few mammalian studies have focused on the integrative physiological actions of neuropeptides on these vital cardio-respiratory regulations. Because both the central neuroanatomical substrates that govern motor ventilatory and cardiovascular output and the primary sequence of regulatory peptides and their receptors have been mostly conserved through evolution, we have developed a trout model to study the central action of native neuropeptides on cardio-ventilatory regulation. In the present review, we summarize the most recent results obtained using this non-mammalian model with a focus on PACAP, VIP, tachykinins, CRF, urotensin-1, CGRP, angiotensin-related peptides, urotensin-II, NPY, and PYY. We propose hypotheses regarding the physiological relevance of the results obtained.